Noble and Precious Metals - Properties, Nanoscale Effects and Applications 2018
DOI: 10.5772/intechopen.70901
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Gold Nanoparticles in Cancer Imaging and Treatment

Abstract: Cancer is one of the leading causes of death worldwide. In the last two decades, the development of nanotechnology has facilitated our ability to design new nanoparticles for the diagnosis and treatment of cancer. In this chapter, we reviewed the applications of gold nanoparticles as contrast agents for cancer imaging, including optical imaging, photoacoustic imaging, and X-ray-based imaging. We also reviewed their applications as delivery carriers for small molecule drugs, therapeutic genes, vaccines, and adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 62 publications
2
23
0
Order By: Relevance
“…Reflecting the presence of gadolinium, a slightly enhanced radiosensitizing effect was observed for AuNP-Gd and AuNP-Gd-BBN, relative to the AuNP-DOTA and to the control. These results are in line with the well-recognized ability of Au and Gd to induce radiosensitizing effects by intensifying the generation of low-energy electrons (e.g., photoelectrons or Auger electrons) upon external irradiation of cells or tissues with photon or proton beams [5,26,32]. Due to the higher cellular internalization observed for the AuNP-Gd-BBN relatively to AuNP-Gd, promoted by the presence of the BBN peptide analogue, it was expected that those nanoparticles would induce additional cellular mortality [28,32,33].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Reflecting the presence of gadolinium, a slightly enhanced radiosensitizing effect was observed for AuNP-Gd and AuNP-Gd-BBN, relative to the AuNP-DOTA and to the control. These results are in line with the well-recognized ability of Au and Gd to induce radiosensitizing effects by intensifying the generation of low-energy electrons (e.g., photoelectrons or Auger electrons) upon external irradiation of cells or tissues with photon or proton beams [5,26,32]. Due to the higher cellular internalization observed for the AuNP-Gd-BBN relatively to AuNP-Gd, promoted by the presence of the BBN peptide analogue, it was expected that those nanoparticles would induce additional cellular mortality [28,32,33].…”
Section: Discussionsupporting
confidence: 85%
“…Due to their unique optical properties, non-toxic nature, relatively simple preparation, and functionalization, gold nanoparticles (AuNPs) are excellent candidates for this type of application. AuNPs are versatile nanoplatforms that can be easily functionalized with several imaging agents, plus biological targeting moieties and drugs, combining therapeutic and diagnostic functions within a single nanoparticle [4][5][6][7][8]. While this concept is auspicious, AuNPs have to overcome multiple hurdles to reach their full potential in clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…[ 80] It has been reported that AuNPs present the following advantages as drug delivery systems:  Large surface area-they offers high loading capacity of drug, improving the drug hydrophilicity and stability (AuNPs can be synthetized in a large board of sizes, from 1 to 150 nm);  Easy surface modification, with targeting ligands to enhance the tumor selective accumulation (the presence of a negative charge on the surface of AuNPs makes them easy to be modified, they can be functionalized easily by the addition of various biomolecules such as drugs, targeting ligands, and genes);  Passive targeting ability to tumor site, due to their leaky neo-vessels (EPR effect);  Controlled release of drugs, in the case of internal or external stimulus [7].…”
Section: Gold Nanoparticles As Drug Delivery Agents Targeted To Cancementioning
confidence: 99%
“…In the last several years, AuNPs (bare or functionalized) have received important attention in nanotherapeutic cancer treatment ( Figure 1) due to their unique properties, which make them suitable candidates for conjugation with targeting ligands, imaging labels, and therapeutic drugs. Also, it has been demonstrated that functionalized AuNPs can be used for targeted molecular imaging and localized surface plasmon resonance (LSPR) [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation